IoT Applications in Agriculture - Jain, Deepak (Indian Journal of Computer Science, 2020)
Agricultural practices have changed over the ages. With increasing population and challenges like climate change, there is lot of pressure on countries to increase yield of crops, make them less prone to damage from climate changes and pests. The green revolution led to an increase in yield of crops, but there is lot of scope for improvement. Technologies like Internet of Things, Big Data and Predictive Analytics are being used for smart farming. This paper discusses various smart farming technologies and their benefits.